2019
DOI: 10.1002/anie.201913644
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Multiple Effects to Enhance Uranium Extraction from Natural Seawater by Black Phosphorus Nanosheets

Abstract: Based on the photoinduced photothermal, photoelectric, and photocatalytic effects of black phosphorus (BP) nanosheets, a BP‐PAO fiber with enhanced uranium extraction capacity and high antibiofouling activity is fabricated by compositing BP nanosheets into polyacrylamidoxime (PAO). The photothermal effect increases the coordination interaction between UO22+ and the functional amidoxime group, and the photoelectric effect produces the surface positive electric field that exhibits electrostatic attraction to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(48 citation statements)
references
References 56 publications
2
44
0
Order By: Relevance
“…The uranium adsorption capacity of NDA‐TN‐AO increased by 33.0 % after 27 days of light irradiation, while the uranium adsorption capacity of BDA‐TN‐AO increased only by 21.2 %, which can be ascribed to the much better photocatalytic and photoelectric activity of NDA‐TN‐AO. Both the NDA‐TN‐AO and BDA‐TN‐AO showed selectivity to uranium and vanadium in seawater, but not other metals (Figure d), consistent with the selectivity of the amidoxime group . Furthermore, the anti‐biofouling behaviors of NDA‐TN‐AO and BDA‐TN‐AO were tested in seawater for a long time.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The uranium adsorption capacity of NDA‐TN‐AO increased by 33.0 % after 27 days of light irradiation, while the uranium adsorption capacity of BDA‐TN‐AO increased only by 21.2 %, which can be ascribed to the much better photocatalytic and photoelectric activity of NDA‐TN‐AO. Both the NDA‐TN‐AO and BDA‐TN‐AO showed selectivity to uranium and vanadium in seawater, but not other metals (Figure d), consistent with the selectivity of the amidoxime group . Furthermore, the anti‐biofouling behaviors of NDA‐TN‐AO and BDA‐TN‐AO were tested in seawater for a long time.…”
Section: Resultssupporting
confidence: 60%
“…This process allowed efficient regeneration of binding sites for further binding of additional U VI . Furthermore, the excellent photoelectric effect of NDA‐TN‐AO could efficiently release electrons from the skeleton and form a surface positive electric field around the NDA‐TN‐AO skeleton, which would show a strong electrostatic attraction to [UO 2 (CO 3 ) 3 ] 4− , further increasing the uranium adsorption capacity …”
Section: Resultsmentioning
confidence: 99%
“…Owing to the excellent photocatalytic activity of Tp‐DBD, it can effectively produce biotoxic ROS, and show a high anti‐biofouling performance by destroying biological entities. [ 5a ] In this study, we used bacteria as targets. The result showed that the Tp‐DBD had an ultra‐high anti‐bacterial activity against the tested bacterial strains (>95%), which is much higher than that of olefin‐linked NDA‐TN‐AO (>85%), [ 6b ] including both Gram‐negative Pseudomonas aeruginosa , and Vibrio alginolyticus , with Gram‐positive Staphylococcus aureus , and Bacillus cereus ( Figure a,c).…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 ] Selective uranium recovery from seawater could satisfy the growing demand for energy. [ 2 ] However, several key bottlenecks seriously hinder selective recovery of uranium from seawater, including abundant competitive ions, [ 3 ] extremely low uranium concentration, [ 4 ] serious biofouling, [ 5 ] and complex marine corrosive environment. [ 6 ] To realize selective recovery of uranium from seawater, adsorbents with high specific affinity, prominent capacity, fast equilibrium rate, anti‐biofouling activity, and long cycle life are required.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Various researches have been developed to use hydrogels as flexible sensors, [24][25][26] supercapacitors, [27] lithium batteries, [28] drug release, [29] actuators, [30] etc. However, due to the evaporation of aqueous solution in hydrogels, [31][32][33] the decreased conductivity and mechanical properties of hydrogels make it difficult to apply the hydrogels to flexible electronics. [34,35] Although some hygroscopic salts have been added to hydrogels to minimize this problem, the evaporation has not been prevented.…”
Section: Introductionmentioning
confidence: 99%